They Will Come, You Must Build It: A Modified Delphi Process Applied to Preparing Acute Care Facilities Infrastructure for High-Consequence Infectious Diseases - Chan, Justin; Searle, Eileen F; Khodyakov, Dmitry; Denson, Logan; Echeverri, Andrea; Browne, Edward M; Chiarelli, Yvonne; Dickey, Linda L; Erickson, Douglas S; Flannery, Jonathan; Kaplan, Lewis J; Markovitz, Sarah; et al. (Health security, 2024)
Patients with suspected or confirmed high-consequence infectious diseases (HCIDs) may present for care at any acute care facility. However, there are limited data to inform recommendations for the design, maintenance, and operation of isolation spaces for patients with suspected or confirmed HCIDs. To address this gap, we developed consensus statements by convening a group of 29 subject matter experts to participate in a modified Delphi process facilitated by a validated tool (the RAND-developed ExpertLens system). The subject matter experts participated in 3 consensus rounds, providing feedback and rating the appropriateness of 36 draft consensus statements. These draft statements were then revised based on their feedback. As a result, we developed 36 consensus statements addressing 5 domains: (1) patient room physical space, (2) doors and windows, (3) air handling, (4) electrical and plumbing, and (5) soiled utility rooms and waste management. These statements could inform the approaches of frontline acute care facilities when building new spaces or modifying existing spaces to enable appropriate HCID patient isolation and care.